ECCENTRICITY, SPACE BENDING, DIMENSION - Nitu, Marian; Smarandache, Florentin; Mircea, Selariu (Italian Journal of Pure and Applied Mathematics, 2014)
The main goal of this paper is to present new transformations, previously non-existent in traditional mathematics, that we call centric mathematics (CM) but that became possible due to the new born eccentric mathematics, and, implicitly, to the supermathematics (SM). As shown in this work, the new geometric transformations, namely conversion or transfiguration, wipe the boundaries between discrete and continuous geometric forms, showing that the first ones are also continuous, being just apparently discontinuous.